Peranan Komunikasi Interpersonal Guru Dalam Meningkatkan Motivasi Belajar Siswa : (Studi Pada Guru – Guru Di SMP Van Lith) - Maria Stella Meinda; A. Munanjar (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
This study aims to determine the Role of Teacher Interpersonal Communication in increasing Learning Motivation at Van Lith Jakarta Junior High School. This research is a descriptive research with a qualitative approach. The research informants consisted of key informants, namely the teachers and students of Van Lith Middle School and supporting informants, namely the students' parents. Data collection techniques obtained by interview techniques, and documentation. Using descriptive qualitative obtained through data analysis known as data processing. The results of the research on the Role of Teacher Interpersonal Communication in Improving Student Learning Motivation (STUDY ON TEACHER AT SMP VAN LITH) are as follows: (1) Establishing Mutual Relationships (2) Increasing Student Learning Motivation (3) Maximizing School Programs (4) Fostering School Extracurriculars (5) Optimizing School Facilities. Obstacles that are often faced are the lack of different student resources and the lack of writing, the lack of parental attention to children, the lack of optimizing online media resulting in many people not knowing detailed school information, service and togetherness at Van Lith Junior High School is good . School programs and school activities have been carried out effectively.